Effect of using ultrasound to break dormancy and germination of xylopia emarginata mart seeds. (Research, Society and Development, 2020)
Xylopia emarginata Mart. is a typical species of gallery forests, characterized by its tolerance to strong water saturation, becoming a potential species for the recovery of riparian ecosystems, thus, evaluating the germination process of this species is of great importance, as it covers technical knowledge about the production of seedlings used in the revegetation of degraded areas. Some seeds have dormancy requiring techniques to accelerate germination. The present study aimed to evaluate the influence of ultrasound bathing on germination and conductivity of the spécies Xylopia emarginata Mart. The seeds were subjected to different immersion times (0, 3, 6, 9, 12, 15 and 18 minutes) in an ultrasonic bath (45 kHz) in distilled water and placed in BOD at 25 ºC to evaluate the electrical conductivity of the solution (50 ml). Then, they were placed to germinate in trays with vermiculite under environmental laboratory conditions for 60 days, to evaluate the percentage of final germination. 30 seeds were used for each of the 6 repetitions. The analysis of variance showed no significant effect (p> 0.05) of the ultrasonic bath on the conductivity and germination of Xylopia emarginata Mart. Seeds, obtaining an average conductivity of 173.32 µS cm-1 at 25 ºC and germination average of 24.27%.